Securing of an IOT Applications: An Analysis of Blockchain based Approach - K Vikram, J Rajeshwar, M V Narayana, K Gautham, D Manasa (International Journal of Control and Automation, 2020)
Beyond the finance industry, Blockchain technology (BT) is being commonly accepted technology. Researchers and professionals alike explore diverse areas of application for innovative origination. The smart city is one such area. Based on BT’s characteristics to enhance the quality of life and institutional processes and environmental protection, entrepreneurs have led the initiative to reduce the negative impacts of urbanization. However, there is a shortage of integrated and border-related research because of entrepreneurial complexities and vast technology fields for BT in intelligent towns. This research aims to build a multi-layer classification that reveals by what means BT is used in various business representations in smart cities. To this end, we found an example of 80 startups selling apps and analyzing their market strategies for smart cities. The blockchain platform has demonstrated exciting potential for usage ever since it was launched. Blockchain has been implemented in several areas, from the original bitcoin to the existing smart contract. While several types of research are emerging on blockchain privacy and security concerns, the reliability of blockchain networks has not been studied extensively. This article carries out a thorough analysis of security risks, analyzing standard blockchain networks, and examining the respective actual attacks. The paper discusses configurations of market structures and technical features of smart city systems in blockchain. Blockchain Technology startups classification models in many fields are Economy Sharing, Internet of Things (IoT), Privacy and Security. This proposal will support academia, professionals, and regulators involved in obtaining fresh perspectives on how BT is used in developing and gaining profit among startups.